The effect of phenylalanine restricted diet on anthropometric parameters in classical phenylketonuria patients - Engin Köse; Hatice Öztürk; Baransel Özdemir; Recep Eren Özçelik; Lütfiye Çiftçi; Kübra Çetin; Fatih Öztürk; Nur Arslan (Galenos Publishing House, 2019)
INTRODUCTION: Classical phenylketonuria (PKU) is an inherited disorder of amino acid metabolism disorder. The basis of treatment is a life-long phenylalanine restricted diet. In this study, we aimed evaluate the the effect of phenylalanine restricted diet on anthropometric parameters of patients with PKU. METHODS: This study was conducted retrospectively in the pediatric nutrition and metabolism clinic between 2007 and 2015 by reviewing the charts of 40 patients with PKU followed by dietary therapy and 78 patients with mild hyperphenylalanine (HPA) without dietary therapy. Body weight, height, weight standard deviation score (SDS), height SDS, Body mass index (BMI) SDS of the patients were assessed at the birth, sixth, twelfth, eighteenth, twenty fourth, thirtieth and thirty-sixth months of life. RESULTS: In the analysis of anthropometric parameters of patients at birth. 6th month. 12th month. 18th month. 24th month. 30th month and 36th month of life there was no differences in weight gain (p=0.516). In the evaluation of height with six months interval, at the end of the 3 years of life, height growth rate was higher in HPA group than PKU group (F(1,33)=3.443,p=0.037). Height growth rate of PKU patients with diet therapy was slower than HPA patients in the first three years of life, but there was no significant difference between the two groups in terms of BMI. DISCUSSION AND CONCLUSION: We can conclude that the height growth rate is lower in PKU patients than HPA patients. We think that the lower height growth rate of PKU patients is the result of Phe and natural protein-restricted diet.